PRICE RELATIONSHIP ANALYSIS, PROMOTION AND SERVICE QUALITY TO IMPROVE CUSTOMER LOYALTY IN CLOTING HARDWARE AT TUNJUNGAN PLAZA SURABAYA - Arif Hidayat Albar; Agus Baktiono (Jurnal Ekonomi, 2018)
The existence of this research is in the background of the instability of the sales volume of the Hardware clothing company in Tunjungan Plaza Surabaya, from the data generated in the last year of 2015 the Hardware clothing company experienced ups and downs in its sales, this has a direct impact on company revenue, with the company's instability. it is feared that it will make the company's performance decline and sustainable unstable. This study aims to determine the level of the relationship between promotional variables, price, service to increase customer loyalty, researchers need to distribute a questionnaire as many as 123 respondents according to the number of members on Hardware clothing. To determine the level of validity of the results of the respondents' answers, the researcher conducted a validity and reliability test. while the data used interval data. The data analysis used Person Product Moment / Pearson Correlation. From the test results and analysis regarding the relationship between promotion, price, and service in increasing customer loyalty, it can be concluded that the three variables have a significant relationship. Of the three variables, the price variable which has a moderate relationship value (0.405) is compared to the promotion (0.256) and service (311) variables which have a low value. From the promotional variables, prices, and services in this study, it can be used as a reference for what variables that are considered low can be increased.